International terrorism, political instability and the escalation effect - Nauro F. Campos; Martin Gassebner (ETH Zurich, KOF Swiss Economic Institute, 2009)
What are the main causes of international terrorism? The lessons from the surge of academic research that followed 9/11 remain elusive. The careful investigation of the relative roles of economic and political conditions did little to change the fact that existing econometric estimates diverge in size, sign and significance. In this paper we present a new rationale (the escalation effect) stressing domestic political instability as the main reason for international terrorism. Econometric evidence from a panel of more than 130 countries (yearly from 1968 to 2003) shows this to be a much more promising avenue for future research than the available alternatives.
Keywords: C25; D72; F59; H56; P48; 330; terrorism; international terrorism; political instability; escalation; Politische Gewalt; International; Politische Stabilität; Welt